Widely tunable black phosphorus mid-infrared photodetector. Issue 1 (December 2017) - Chen, Xiaolong; Lu, Xiaobo; Deng, Bingchen; Sinai, Ofer; Shao, Yuchuan; Li, Cheng; Yuan, Shaofan; Tran, Vy; Watanabe, Kenji; Taniguchi, Takashi; Naveh, Doron; Yang, Li; et al.
Abstract Lately rediscovered orthorhombic black phosphorus (BP) exhibits promising properties for near- and mid-infrared optoelectronics. Although recent electrical measurements indicate that a vertical electric field can effectively reduce its transport bandgap, the impact of the electric field on light-matter interaction remains unclear. Here we show that a vertical electric field can dynamically extend the photoresponse in a 5 nm-thick BP photodetector from 3.7 to beyond 7.7 μm, leveraging the Stark effect. We further demonstrate that such a widely tunable BP photodetector exhibits a peak extrinsic photo-responsivity of 518, 30, and 2.2 mA W−1 at 3.4, 5, and 7.7 μm, respectively, at 77 K. Furthermore, the extracted photo-carrier lifetime indicates a potential operational speed of 1.3 GHz. Our work not only demonstrates the potential of BP as an alternative mid-infrared material with broad optical tunability but also may enable the compact, integrated on-chip high-speed mid-infrared photodetectors, modulators, and spectrometers. The bandgap of ultrathin black phosphorus can be tuned by a vertical electric field. Here, the authors leverage such electric field to extend the photoresponse of a black phosphorus photodetector to 7.7 μm, opening the doors to various mid-infrared applications.